TIGIT deficiency promotes autoreactive CD4+ T-cell responses through a metabolic‒epigenetic mechanism in autoimmune myositis - Yimei Lai; Shuang Wang; Tingting Ren; Jia Shi; Yichao Qian; Shuyi Wang; Mianjing Zhou; Ryu Watanabe; Mengyuan Li; Xinyuan Ruan; Xin Wang; Lili Zhuang; et al. (Nature Communications)
Abstract Polymyositis (PM) is a systemic autoimmune disease characterized by muscular inflammatory infiltrates and degeneration. T-cell immunoreceptor with Ig and ITIM domains (TIGIT) contributes to immune tolerance by inhibiting T cell-mediated autoimmunity. Here, we show that a reduced expression of TIGIT in CD4+ T cells from patients with PM promotes these cells’ differentiation into Th1 and Th17 cells, which could be rescued by TIGIT overexpression. Knockout of TIGIT enhances muscle inflammation in a mouse model of experimental autoimmune myositis. Mechanistically, we find that TIGIT deficiency enhances CD28-mediated PI3K/AKT/mTOR co-stimulatory pathway, which promotes glucose oxidation, citrate production, and increased cytosolic acetyl-CoA levels, ultimately inducing epigenetic reprogramming via histone acetylation. Importantly, pharmacological inhibition of histone acetylation suppresses the differentiation of Th1 and Th17 cells, alleviating muscle inflammation. Thus, our findings reveal a mechanism by which TIGIT directly affects the differentiation of Th1 and Th17 T cells through metabolic‒epigenetic reprogramming, with important implications for treating systemic autoimmune diseases.